Coagulase positive Staphylococci contamination and the risk associated with the production of toxin in foods - An Exploratory Study : Coagulase-positive Staphylococcus contamination in foods - R, Naveen Kumar; Nagella, Balakrishna; Vemula, Sudershan Rao; Putchaa, Uday Kumar (Indian Journal of Dairy Science, 2024)
Food-borne diseases pose a threat to human health and the economy of individuals, families, and nations. Staphylococcus aureus is one of the most common causes of foodborne intoxications in most countries of the world. The present study was done to analyze the extent of Staphylococci contamination and the risk associated with the production of toxins in foods. A total of 450 Food samples were collected from retail markets, sweet shops, and households in Hyderabad. Among 143 (31.7%) cultures of Staphylococci, 106 (74.1%) showed coagulase enzyme production and 37 (25.9%) isolates were coagulase-negative. Only nine cultures (6.3%) showed a positive result for enterotoxin production. It is known that >106 CFU/g of S. aureus is likely to produce an enterotoxin, however, in the present study 17% of food samples have crossed the limit but a very less number of them were able to produce enterotoxin. For the risk assessment of S. aureus contamination in foods, coagulase test and toxin production of isolates have to be evaluated. The data will be helpful in setting standards for the microbiological quality of foods.